2018
DOI: 10.1021/acs.jpcc.8b08343
|View full text |Cite
|
Sign up to set email alerts
|

Isothermal Stimulation of Mineral Dissolution Processes by Acoustic Perturbation

Abstract: On the basis of systematic experimental interrogation of the aqueous dissolution behavior of a large selection of minerals, whose dissolution rates vary by several orders of magnitude, this study demonstrates that acoustic perturbation yields an unprecedented enhancement in dissolution kinetics, which scales with the mineral's hardness and average bond energy. The dissolution enhancement produced is described by an Arrhenius-like formulation that reveals the energy imparted to the solute's surficial atoms by s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
28
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(31 citation statements)
references
References 45 publications
3
28
0
Order By: Relevance
“…The observation that the reduction in apparent activation energy is solely proportional to the number of weak constraints (i.e., the curve passes through the origin) originates from the fact that a solid with no ("zero") weak constraints (e.g., quartz 69 ) would not exhibit any decrease in apparent activation energy since no constraint would be broken upon sonicationwhich agrees with earlier studies that found no dissolution enhancement of quartz when exposed to ultrasonic stimulation. 16,18 Crucially, a plot of ΔE a vs the number of strong constraints per atom (not shown) gives a y-intercept of −19 kJ/mol, demonstrating that if no strong constraints were present, the activation energy reduction by sonication would be significantly different from zero. These results suggest that Si extraction from minerals is essentially a bond-breakage process.…”
Section: Topological Origin Of the Decrease In Apparent Activation En...mentioning
confidence: 99%
See 3 more Smart Citations
“…The observation that the reduction in apparent activation energy is solely proportional to the number of weak constraints (i.e., the curve passes through the origin) originates from the fact that a solid with no ("zero") weak constraints (e.g., quartz 69 ) would not exhibit any decrease in apparent activation energy since no constraint would be broken upon sonicationwhich agrees with earlier studies that found no dissolution enhancement of quartz when exposed to ultrasonic stimulation. 16,18 Crucially, a plot of ΔE a vs the number of strong constraints per atom (not shown) gives a y-intercept of −19 kJ/mol, demonstrating that if no strong constraints were present, the activation energy reduction by sonication would be significantly different from zero. These results suggest that Si extraction from minerals is essentially a bond-breakage process.…”
Section: Topological Origin Of the Decrease In Apparent Activation En...mentioning
confidence: 99%
“…Acoustic stimulation produces chemical and physical effects through cavitation and can greatly expedite dissolution 56 by reducing activation barriers associated with (net) reactions. 16 Herein, isothermal slag dissolution was carried out at temperatures from 25 to 60 °C (i.e., to match Figure 2c) for a fixed vibration amplitude, i.e., 60 μm, of the horn tip. The rate enhancement of Si-dissolution by sonication as a function of temperature is shown in Figure 2d.…”
Section: Dissolution Kineticsmentioning
confidence: 99%
See 2 more Smart Citations
“…[26][27][28][29] Therefore, with a specic goal of enhancing waste utilization, resource recovery and reutilization, and circular economy, we demonstrate an approach to extract Ca-from alkaline industrial wastes, 30,31 and produce Ca(OH) 2 via a calcination-free process. While herein we focus on alkaline industrial wastes, of course, the broad contours of this process are also applicable to alkaline rock species, which although harder to solubilize unless externally stimulated, 32,33 offer the potential to offer a near-limitless source for alkaline element extraction.…”
Section: Introductionmentioning
confidence: 99%